Geochemical transformations of sulfur and their role in the formation of different types and subtypes of saline lakes in Southeastern Transbaikalia - S. V. Borzenko; I. A. Fedorov (Applied Water Science, 2024)
Abstract This study focused on the chemistry and isotopes of sulfur in lakes. The bottom sediments and water columns of lakes were found to contain reduced forms of sulfur, including hydrogen sulfide ions, elemental sulfur, and thiosulfate ions, along with sulfate ions. It was determined that elemental sulfur in lakes is present mainly in the form of suspensions and colloids, and the proportion of elemental sulfur in polysulfides increases with increasing water pH. It was shown that sulfate reduction results in the greatest isotope fractionation, with a light sulfur isotope accumulating in hydrogen sulfide ions and a heavy sulfur isotope accumulating in sulfate ions. It was confirmed that the abiotic reaction of hydrogen sulfide with oxygen yields a mixture of products that are depleted in 34S and enriched in 34S in hydrogen sulfide. In contrast, the microbial oxidation of HS− → S0 yields zerovalent sulfur, which is 2–4‰ heavier than the initial product. It was shown that the loss of sulfate ions due to bacterial reduction is most significant in subtype-I and subtype-III chloride and soda lakes. In contrast, in subtype-II sulfate and soda lakes, an increase in sulfate ions was noted due to the oxidation of hydrogen sulfides in water-bearing rocks and bacterial hydrogen sulfide. This finding indicated that in addition to evaporation, the formation of a particular type and subtype of saline lake involves the processes of aluminosilicate hydrolysis, sulfate reduction and hydrogen sulfide oxidation.